บทบาททางการเมืองของผู้นำท้องถิ่น : ศึกษากรณีผู้นำท้องถิ่นในจังหวัดชลบุรี - ยรรยง สุวรรนาวุธ (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
This study of political role of local leaders places its imphasis on the expected and actual role of the local leaders in Chon Buri Province. Apart from the focus on the difference between the two types of political role, it also looks at the associations between some political, economic and social factors and the political role. Based on the data collected from 400 samples, this study finds, a moderate level of the leaders actual role and a high level of their expected role. The highest role, both expected and actual is in local election, while the lowest one in their relationship with political parties. In comparson between their actual and expected role, a significant difference is discovered in every aspect of the local leaders role. However among the political, economic and social fectors only occupation has a significant association with the two types of political role.